2008
DOI: 10.1111/j.1365-2656.2008.01485.x
|View full text |Cite
|
Sign up to set email alerts
|

Skipping the Baltic: the emergence of a dichotomy of alternative spring migration strategies in Russian barnacle geese

Abstract: Summary 1.Since the early 1990s, an increasing proportion of barnacle geese, Branta leucopsis , bound for breeding sites in the Russian Arctic delay their departure from the wintering quarters in the Wadden Sea by 4 weeks. These late-migrating geese skip spring stopover sites in the Baltic traditionally used by the entire population. 2. Individual geese from an arctic colony tracked by satellite or light-level geolocators during spring migration in 2004 and 2005 predominantly followed the new strategy, but a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(99 citation statements)
references
References 44 publications
6
92
0
1
Order By: Relevance
“…Th is relationship between timing of northbound and southbound migration, which lacks a clear theoretical foundation in migration literature 16 , may refl ect constraints operating on the entire annual cycle. Although fl exibility in duration and investment in annual activities such as moult 32,33 and fuelling 34 , and even in migration route 35 , have been demonstrated in other species, the extreme nature of the godwit ' s migration may naturally ensure reduced variation in these parameters. Accordingly, the specifi city with which breeding site dictates migration timing and the rigid repeatability of individual migration schedules 19 seem especially high, compared with those found in shorter-distance migrant birds.…”
Section: Discussionmentioning
confidence: 99%
“…Th is relationship between timing of northbound and southbound migration, which lacks a clear theoretical foundation in migration literature 16 , may refl ect constraints operating on the entire annual cycle. Although fl exibility in duration and investment in annual activities such as moult 32,33 and fuelling 34 , and even in migration route 35 , have been demonstrated in other species, the extreme nature of the godwit ' s migration may naturally ensure reduced variation in these parameters. Accordingly, the specifi city with which breeding site dictates migration timing and the rigid repeatability of individual migration schedules 19 seem especially high, compared with those found in shorter-distance migrant birds.…”
Section: Discussionmentioning
confidence: 99%
“…eagle Haliaeetus albicilla has been suggested as a possible explanation for the recent 380 change in migratory habits of barnacle geese Branta leucopsis where the majority of 381 birds no longer use stopover sites in the Baltic region that were traditionally used by 382 the entire population (Eichhorn et al 2009). Another possible explanation is that the 383 strong population growth among the geese have led to increased competition which in 384 turn have caused reduced energy deposition rates at the Baltic stopover sites below 385 the limit of usefulness in time-selected migration (Eichhorn et al 2009, see next 386 section).…”
Section: Ydenberg 2003) 341mentioning
confidence: 99%
“…Another possible explanation is that the 383 strong population growth among the geese have led to increased competition which in 384 turn have caused reduced energy deposition rates at the Baltic stopover sites below 385 the limit of usefulness in time-selected migration (Eichhorn et al 2009, see next 386 section). Applying a dynamic model to this case, Jonker et al (2010) showed in an 387 elegant way that both explanations are possible but also that the use of the Baltic 388 stopover area was particularly sensitive to predation danger.…”
Section: Ydenberg 2003) 341mentioning
confidence: 99%
See 1 more Smart Citation
“…These geese migrate in May-early June toward their breeding grounds via staging sites located in the Baltic Sea (most notably on the Swedish island of Gotland and in western Estonia), the White Sea and on the Kanin Peninsula (Eichhorn et al, 2006;Eichhorn et al, 2009;Madsen et al, 1999). The geese usually spend almost 2 weeks in the White Sea area, or in other areas closer to their breeding sites.…”
Section: Study Populationsmentioning
confidence: 99%